AKIBAT HUKUM PENCABUTAN BERITA ACARA PEMERIKSAAN SAKSI DI DEPAN PERSIDANGAN DALAM TINDAK PIDANA NARKOTIKA (Studi Putusan Nomor 201/Pid.Sus/2018/PN Simalungun) - Pondang Hasibuan; Sahat Benny Risman Girsang; Erni Juniria Harefa; Janpatar Simamora; Herlina Manullang (Nommensen Journal of Legal Opinion, 2020)
During the trial, witnesses were often found retracting the testimony of witnesses given during the investigation (Police) in court. There are many reasons that the revocation is given by the witness to revoke the witness's BAP that has been given before the investigator. The problem studied is how the consequences of the revocation of the BAP in front of the trial affect the judge's decision in Decision No. 201/Pid.Sus/2018/PN Simalungun. The research method uses a normative juridical approach, which is an approach based on the main legal material by examining theories, concepts, legal principles and legislation. In Decision No. 201/Pid.Sus/2018/PN Sim that the strength of the evidence of the witness's BAP becomes an integral part of the investigation file and is finally transferred to the District Court for trial, it has become evidence of affidavits. That the consequence of the revocation of the witness's BAP before the trial in Decision No. 201/Pid.Sus/2018/PN.Sim did not affect the judge's decision to convict the defendant, because the Panel of Judges considered that the revocation of the witness's BAP did not have a strong reason and the defendant's actions were also categorized as extraordinary crime.